Analisa Pembiayaan Dari Sisi Karakter, Kemampuan Usaha dan Permodalan Debitur Terhadap NPF - nasfi, nasfi; Asnah, Asnah (El-kahfi | Jurnal Ekonomi Islam, 2022)
The purpose of the study was to determine the effect of the debtor's character (mudharib), the debtor's business ability and debtor's capital on the NPF (Non-Performing Financing) of the Sharia People's Financing Bank (BPRS) headquartered in Agam Regency. This research is a quantitative research with the number of respondents 66 debtors in the city of Bukittinggi and Agam Regency who were randomly selected with data collection techniques using questionnaires. For the analysis tool using Structural Equation Modeling Software based on Partial Least Squere (SEM-PLS). The results showed that the character of the debtor had a significant positive effect on the NPF of Islamic people's financing banks, the business ability of the debtor had a significant positive effect on the NPF of Islamic people's financing banks and the debtor's capital had a significant effect on the NPF of Islamic people's financing banks, where the proposed hypothesis was accepted. Debtor's character, debtor's business ability and debtor's capital affect Non-Performing Financing in BPRS.